Advances in Transboundary Aquifer Assessment (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
“Advances in Transboundary Aquifer Assessment” features studies of transboundary aquifers, particularly at the border shared by Mexico and the United States, a semi-arid to arid region experiencing significant population growth and changing climate conditions. Aquifer assessment in a transboundary setting requires the cooperation of multiple jurisdictions, sometimes with different languages and cultures. The papers in this Special Issue represent a broad array of investigations of complex physical aquifer systems and related institutional settings, including identification and prioritization of needs and strategies for sustainable groundwater development and use; characterization of the physical framework of the aquifer, stressors on the aquifer system, and how those stressors influence the availability of groundwater in terms of its quantity and quality; and the incorporation of stakeholder input and prioritization directly into the process of aquifer assessment and model building.